ANALISIS USAHA TAMBAK DI TANJUNG AJU DESA TANI BARU KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Lailan Horiah Effendy; Dayang Diah Fidhiani; Heru Susilo (Jurnal Pembangunan Perikanan dan Agribisnis, 2014)
This research aims to determine the cost, revenue and profit of the pond enterprise in Tanjung Aju of Tani Baru Village in Anggana District.The results showed that cost of the enterprise was calculated for Rp 562.653.500,00 per year or an average of Rp 38,803,690 per year per respondent. In addition, the revenue received from the enterprise was accounted for Rp 1.476.021.000,00 per year or an average of Rp 101.794.552,00 per year per respondent. It can be concluded that pond farming in the study location was beneficial as their total revenue was bigger than total cost and the farming enterprise is suggested to be continued.